McMYB10 regulates anthocyanins and quercetin accumulation during the fruit development of crabapples. Issue 4 (4th July 2017) - Lu, By Yanfen; Hao, Suxiao; Bu, Yufen; Yang, Shaolan; Zhang, Jie; Liu, Liqiang; Yao, Yuncong
ABSTRACT: Crabapple ( Malus spp.) trees constitute an important worldwide germplasm resource with high ornamental, agricultural, and nutritional value. The content and composition of flavonoids in fruits are major determinants of the colouration and nutritional value of fruits; however, the mechanisms of red colouration and flavonoid biosynthesis in crabapple fruits are not yet fully understood. Two crabapple cultivars, the ever-red fruited 'Royalty' and the green-to-red fruited 'Flame', were studied during fruit development. In both cultivars, our results showed that the McMYB10 transcript level is associated with fruit colouration and anthocyanin and quercetin contents in fruit peel during fruit development. Shading treatments affected fruit colouration by regulating the expression levels of McMYB10 in 'Royalty'. Transient over-expression of McMYB10 in crabapple fruit promoted transcription of some flavonoid biosynthetic genes and induced anthocyanin and quercetin accumulation and red colouration in crabapple fruits. Our study indicates that McMYB10 is a key regulator of anthocyanin and quercetin biosynthesis during crabapple fruit development.